(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This article provides an overview of semantic analysis, a process crucial for understanding the meaning of text within a given context. It delves into the key components of semantic analysis, including word meaning, contextual understanding, syntactic structure, pragmatic considerations, and cultural factors. Through this exploration, the article highlights the importance of going beyond literal interpretation to uncover deeper layers of meaning, associations, and cultural nuances embedded in language.